Dual apprenticeship and continuing vocational education and training in Central and Eastern Europe: Opportunities and obstacles for German family businesses - Michael Gessler; Susanne Peters (Stiftung Familienunternehmen, 2022)
The growth potential for family businesses in Central and Eastern Europe is vast, but skilled workers are in short supply. The study Dual Apprenticeship and Continuing Vocational Education and Training in Central and Eastern Europe examines for the first time how family businesses in the region are providing vocational training and offers recommendations for action.
Keywords: 330